2008
DOI: 10.1002/hed.20790
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Accuracy of imaging tests in the diagnosis of recurrent laryngeal carcinoma after radiotherapy

Abstract: The diagnostic accuracy of 18FDG-PET is promising and warrants a randomized trial comparing a strategy based on conventional diagnostic work-up to one based on 18FDG-PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 85 publications
0
39
0
Order By: Relevance
“…Both false-negative patients, however, had a previous history of radiotherapy treatment and it is known that previous (chemo)radiotherapy may impair the diagnosis of recurrence and that the most reliable technique to obtain a histological diagnosis would be via microlaryngoscopy under general anaesthesia [15]. The assessment of recurrent laryngeal carcinoma after (chemo)radiotherapy is much more difficult than the assessment of "de novo" carcinoma either by endoscopy or by imaging studies for various reasons: tumour may recur after radiation therapy in multicentric foci, undetectable by imaging studies, residual inflammation changes may be associated with radiotherapy, tumour recurrence may be localised submucosally and invisible during endoscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both false-negative patients, however, had a previous history of radiotherapy treatment and it is known that previous (chemo)radiotherapy may impair the diagnosis of recurrence and that the most reliable technique to obtain a histological diagnosis would be via microlaryngoscopy under general anaesthesia [15]. The assessment of recurrent laryngeal carcinoma after (chemo)radiotherapy is much more difficult than the assessment of "de novo" carcinoma either by endoscopy or by imaging studies for various reasons: tumour may recur after radiation therapy in multicentric foci, undetectable by imaging studies, residual inflammation changes may be associated with radiotherapy, tumour recurrence may be localised submucosally and invisible during endoscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is also valuable in the investigation of patients with unknown primary, e.g., patients presenting only with neck mass. In addition, FDG-PET is used for followup after treatment when searching for recurrent disease or metastasis (3)(4)(5). However, FDG-PET has some inherent problems.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated a sensitivity of 89% and specificity of 74% of the PET-CT to differentiate between tumor recurrence and local actinic late alterations. It should therefore be the exam of choice to avoid unnecessary CT scans and laryngoscopies with biopsies 42,43,45 . The various treatments proposed for chondroradionecrosis included the use of antibiotic therapy, air humidifiers, corticosteroids, antireflux drugs (proton pump blockers, prokinetics) and hyperbaric chamber (HBC), the latter being in varied regimens.…”
Section: Discussionmentioning
confidence: 99%